FEATURES OF INVESTMENT ACTIVITY IN THE CONSTRUCTION FIELD OF UZBEKISTAN IN MODERN ECONOMIC CONDITIONS - Mirisaev Abdurakhman Abdulahatovich (Лучшие интеллектуальные исследования, 2024)
Abstract: The present article discusses issues on the investment activity in the field of construction and analyzes its features in the modern economic conditions. The general assessment of the investment and construction activities state in modern economic conditions is provided. Alongside with this, the key trends for development and improvement of construction industry are determined.